Association of interaction between mental health literacy and non-suicidal self-injury with suicidal behaviors among middle school students: a cross- sectional survey in three China cities - Zhi-xian ZHANG; Xue-xue HUANG; Jie HU (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To investigate the association of interaction between mental health literacy (MHL) and non-suicidal self-injury (NSSI) with suicidal behaviors among middle school students in China. MethodsWith multistage cluster sampling, totally 17 000 students were recruited from 39 middle schools in three China cities (Beijing, Zhengzhou of Henan province, and Yangjiang of Guangdong province) for self-administered anonymous survey during October 2020 - June 2021. Two scales compiled by Chinese researchers (Adolescent Mental Health Literacy Assessment Questionnaire [AMHLAQ] and Adolescent Non-suicidal Self-injury Assessment Questionnaire [ANSAQ] and a self- designed questionnaire were adopted in the survey. Multivariate logistic regression model was used to explore the association of interaction between MHL and NNSI with suicidal behavior in the students. ResultsAmong the 16 853 students with valid responses, 31.3%, 16.3% and 7.5% reported ever having suicidal ideation, plan and attempt during past one year and the overall self-reported rate of NSSI was 28.9%. Multivariate logistic regression analyses revealed that inadequate MHL and NSSI are risk factors for suicidal ideation, plan and attempt. Furthermore, MHL and NSSI could exert an additive or multiplicative interactive effect on suicidal-related behaviors. ConclusionAmong middle school students in China, suicidal-related behaviors is relatively prevalent and inadequate MHL and NSSI are risk factors for suicidal ideation, suicidal plan and suicidal attempt; the interaction between the two risk factors could increase the risk of suicide-related behaviors.